2011
DOI: 10.1007/s12565-011-0123-9
|View full text |Cite
|
Sign up to set email alerts
|

Structural arrangement of collagen fibrils in the periarterial connective tissue of the kidney: their functional relevance as a structural stabilizer against arterial pressure

Abstract: Periarterial connective tissue with a moderate amount of collagen fibrils is known to be a specialized domain in the renal interstitium. This study aimed to clarify the microscopic architecture of the periarterial connective tissue as a mechanical supportive structure of the intrarenal arteries. Transmission and scanning electron microscopy revealed two populations of collagen fibrils in the periarterial connective tissue. The major one was composed of many bundles of collagen fibrils running in longitudinal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 18 publications
2
12
0
Order By: Relevance
“…The amount of collagen bundles increased as the arteries became larger both in the kidney and skeletal muscle, indicating an increase of mechanical stress by an incremental increase of wall tension in larger arteries, as shown in a previous study [2]. It was also shown that the diameter of collagen fibrils increased as the arteries became larger in the kidney, corresponding to increases of mechanical stress [2], and that in skeletal muscle the collagen fibrils were thicker in larger arteries than in smaller arteries, although quantitative analysis was not performed due to an inadequate sample size.…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…The amount of collagen bundles increased as the arteries became larger both in the kidney and skeletal muscle, indicating an increase of mechanical stress by an incremental increase of wall tension in larger arteries, as shown in a previous study [2]. It was also shown that the diameter of collagen fibrils increased as the arteries became larger in the kidney, corresponding to increases of mechanical stress [2], and that in skeletal muscle the collagen fibrils were thicker in larger arteries than in smaller arteries, although quantitative analysis was not performed due to an inadequate sample size.…”
Section: Discussionsupporting
confidence: 78%
“…The parallel arrangement of the smooth muscle cells of arteries in circular directions was reported in the kidney by the present authors [2,19] and in the muscular arteries in the lung, whereas the elastic arteries in the lung possess several layers of smooth muscle cells arranged in parallel but in different orientations depending on the layers [5]. The muscular arteries in the other organs were reported to possess different arrangements.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations